Post-operative delirium in different age groups and subtypes: a systematic review of case reports - Guo, Jiaming; Guo, Xiaomei; Liu, Wei; Zhou, Aoran; Han, Jiayi; Yi, Runxin; Dong, Lijuan; Zhou, Yinhao (Frontiers in Neurology, 2024)
Aims To explore the clinical presentations and outcomes among different ages and subtypes of post-operative delirium patients. Design Systematic review of Published Cases. Methods and data sources We comprehensively searched PubMed, EMBASE, and MEDLINE for published case reports of post-operative delirium up to April 2023. The systematic review has been registered with PROSPERO. Two researchers independently conducted unblinded reviews of the full-text articles. Results This study included 116 patients with post-operative delirium. Compared to post-operative delirium patients aged 65 and above, those between 18 and 65 years old have lower rates of a history of hypertension, cardiovascular disease and urinary system disorder comorbidities, as well as higher usage rates of fentanyl analogs and lorazepam. Additionally, these patients exhibit lower incidences of anemia and renal failure, along with a lower mortality rate. Compared to post-operative delirium patients aged 65 and above, those under 18 years old have a higher rate of fentanyl analog usage and a higher incidence of post-operative delirium following neurological surgeries. Among the hypoactive, hyperactive, and mixed subtypes, the reasons for surgery, such as cardiovascular diseases, reproductive system diseases, and neurological disorders, significantly varied among these three subtypes. Furthermore, substance abuse history and medication usage patterns also significantly varied among these three subtypes. Conclusions Our investigation has revealed noteworthy insights into post-operative delirium in different patient populations. Notably, age emerged as a pivotal factor. Compared to elderly patients (≥65 years), those aged 18 to 65 demonstrate better prognosis. Additionally, patients younger than 18 years with post-operative delirium have a higher incidence of delirium following neurosurgical procedures compared to those elderly patients. Additionally, a strong association was found between a history of substance abuse and hyperactive delirium. Variations in drug use patterns were observed across different subtypes. Importantly, post-operative delirium patients younger than 18 years, as well as those aged 18 to 65 with mixed-subtype delirium, exhibited similar high mortality rates as elderly patients. This underscores the need for increased attention to post-operative delirium patients under 65 and highlights the necessity of rapid identification and early intervention for these populations at risk of poor outcomes. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023473383, Identifier [Registration ID: CRD 42023473383].